Healthcare-Seeking behavior for sexually transmitted infections among women who initiated sexual intercourse at an early age in 22 Sub-Saharan African Countries: a multilevel analysis of 2018–2024 demographic and health survey data - Getachew Teshale; Melak Jejaw; Kaleb Assegid Demissie; Nebebe Demis Baykemagn; Tirualem Zeleke Yehuala; Jenberu Mekurianew Kelkay (BMC Infectious Diseases)
Abstract Introduction Sexually transmitted infections (STIs) represent a significant global public health concern, contributing substantially to illness and mortality, particularly in Sub-Saharan Africa (SSA). Women of reproductive age who initiated sexual intercourse at an early age are at high risk of acquiring STIs. However, comprehensive data on their care-seeking behaviors in SSA are lacking. This study determines the prevalence of STI-related care-seeking behavior and identifies associated factors among these women. Method This study utilized data from the most recent Demographic and Health Surveys (DHS) conducted in 22 SSA countries between 2018 and 2024. A weighted sample of 54,425 reproductive-age women who initiated sexual intercourse at an early age and reported STIs or related symptoms in the past year was analyzed. A multilevel mixed-effects logistic regression model identified individual and community-level factors, with statistical significance set at *p* < 0.05. Adjusted odds ratios (AORs) with 95% confidence intervals (CIs) were calculated. Results The pooled prevalence of STI-related care-seeking behavior among women initiated sexual intercourse at early age in SSA countries was 39.18% (95% CI: 33.25%, 45.03%). Multilevel analysis revealed significant associations with age, education, religion, pregnancy status, employment, household wealth, media exposure, financial barriers, awareness of AIDS/STIs, cervical cancer testing, residence, community education, media exposure, and poverty. Conclusion STI-related care-seeking behavior remains lower in this population compared to other studies. Associated factors include age, education, religion, pregnancy status, employment, household wealth, media exposure, financial barriers, awareness of AIDS/STIs, cervical cancer testing, residence, and community-level factors such as education, media exposure, and poverty. Public health efforts should prioritize socioeconomically disadvantaged women by strengthening counseling and awareness during cervical cancer screenings and antenatal visits. Policies to improve healthcare access and financial support for these women are essential.